A novel method using a differential staining fluorescence microscopy (DSFM) to track the location of enteric pathogens within mixed-species biofilms - Qiyue Chen; Rong Wang; Joseph M. Bosilevac; Manita Guragain; Sapna Chitlapilly Dass (Scientific Reports, 2023)
Abstract This study developed a new tool, differential staining fluorescence microscopy (DSFM), to measure the biovolume and track the location of enteric pathogens in mixed-species biofilms which can pose a risk to food safety in beef processing facilities. DSFM was employed to examine the impact of pathogenic bacteria, Escherichia coli O157:H7 and three different Salmonella enterica strains on mixed-species biofilms of beef processing facilities. Fourteen floor drain biofilm samples from three beef processing plants were incubated with overnight BacLight stained enteric pathogens at 7 °C for 5 days on stainless steel surface then counter-stained with FM-1-43 biofilm stain and analyzed using fluorescence microscopy. Notable variations in biovolume of biofilms were observed across the fourteen samples. The introduction of E. coli O157:H7 and S. enterica strains resulted in diverse alterations of biofilm biovolume, suggesting distinct impacts on mixed-species biofilms by different enteric pathogens which were revealed to be located in the upper layer of the mixed-species biofilms. Pathogen strain growth curve comparisons and verification of BacLight Red Stain staining effectiveness were validated. The findings of this study show that the DSFM method is a promising approach to studying the location of enteric pathogens within mixed-species biofilms recovered from processing facilities. Understanding how foodborne pathogens interact with biofilms will allow for improved targeted antimicrobial interventions.